Use of water-Cherenkov detectors to detect Gamma-Ray-Bursts at the Large Aperture GRB Observatory (LAGO) - Allard, D.; Allekotte, Ingomar; Alvarez, C.; Asorey, Hernán Gonzalo; Barros, H.; Bertou, Xavier Pierre Louis; Burgoa, O.; Gomez Berisso, Mariano; Martinez, O.; Miranda Loza, P.; Murrieta, T.; Perez, G.; et al. (Elsevier Science, 2008)
Fil: Allard, D.. Université Paris Diderot - Paris 7; Francia